Electronic tongue made of gelatin self-supporting films on printed electrodes to detect lactose - Piccinin, Ana C. V.; Coatrini-Soares, Andrey; Franco, Giuliana T.; Bondancia, Thalita J.; Coatrini-Soares, Juliana; Oliveira, Osvaldo N.; Mattoso, Luiz H. C. (Frontiers in Sensors, 2024)
An electronic tongue was developed for the detection of lactose content in commercial foods. This was accomplished by employing optimized detection units comprised of gelatin films and information visualization methods for data analysis. The films incorporating gelatin, tannic acid, and zein, served as the basis for the sensors, whose electrodes were screen printed using carbon black ink. Self-supporting films were produced using various combinations of these materials, some of which had limited solubility in water (from 33% to 36%). They were hydrophobic and yielded reproducible electrical impedance spectra to be used as sensing units. Lactose detection experiments were conducted using various standard concentrations and commercial food samples. Capacitance decreased with lactose concentration at low frequencies, with films lacking a hydrophobic coating showing higher capacitance signals (exceeding 200 nF). Low limits of detection were obtained for the most sensitive films, as low as 2.03×10 -19 mol/L, comparable to existing biosensors to detect lactose. Combining data from four sensing units in an electronic tongue allowed for the differentiation of lactose concentrations ranging from 1×10 -20 mol/L to 1×10 -6 mol/L using the interactive document mapping (IDMAP) projection technique, leading to a silhouette coefficient of 0.716. The discriminatory power of the electronic tongue was validated by distinguishing between lactose-containing and lactose-free food products. These findings highlight the potential of of electronic tongues made with sustainable materials for applications in food quality assessment and lactose intolerance management.